A New Method to Non-Fragile Piecewise H∞ Control for Networked Nonlinear Systems With Packet Dropouts - Li, Lingchun; Zhang, Guangming; Ou, Meiying (IEEE access, 2020)
This article is concerned with the non-fragile piecewise static output control problem of nonlinear networked control systems with packet dropouts. The Takagi-Sugeno fuzzy approach is used to model the nonlinear networked control systems. Then two stochastic variables subject to Bernoulli random-binary distribution are introduced to describe the packet dropouts of the communication channels between the physical plant and controller. Based on piecewise Lyapunov function and Finsler lemma, sufficient conditions are established via a set of linear matrix inequalities to guarantee the resulting closed-loop system to be stochastically stable with a required H_∞ disturbance attenuation level. Finally, the effectiveness of the proposed method is illustrated by two numerical examples.